Retrospective Analysis of Complications Associated with Laparoscopic Cholecystectomy for Symptomatic Gallstones - Amreek, FNU (Cureus, 2019)
Introduction Gallstones are the major cause of global morbidity. Laparoscopic approach has well-established advantages as compared to the conventional open procedure. It promises better recovery, lower morbidity, and lower postoperative pain, shortens the duration of hospital stay, and has a lower mortality rate. The aim of this study is to assess the frequency of complications in laparoscopic cholecystectomies indicated for symptomatic gallstones and also evaluate the rate of conversion. Methods In this retrospective analysis, all records of laparoscopic cholecystectomy, in patients of age ≥18 years, for symptomatic gallstones, from January 2015 till December 2018 in one of the largest public tertiary care hospitals in Pakistan were included. Results The rate of complications associated with laparoscopic cholecystectomy was 6.8%. Older age, obesity, and multiple pre-operative risk factors were associated with complications. The most common intra-operative complication was hemorrhage (1.3%) and most common postoperative complication was surgical site infection (2.7%). Our conversion rate was 3.6%. Both intra-operative and postoperative complications were more common in procedures which were converted to open. Conclusion The rate of complication and conversion to open in laparoscopic cholecystectomy is not very high. Older age, obesity, and multi-morbidity was associated with complications. Complicated procedures were more commonly needed to be converted to open.